TINJAUAN SISTEMATIS SISTEM INFORMASI KESEHATAN BERBASIS WEB UNTUK TRANSFORMASI MANAJEMEN PENYAKIT KRONIS - Askar Saputra; Sri Rejeki; Eriska Amalia Sakkar; Sriyanti Azzahra; Adel Asti Ananta; Dayanti Dayanti (Plexi Digital Indonesia, 2026)
Chronic diseases require effective long-term management, and advances in information technology have promoted the use of web-based health information systems to support chronic disease care. This study presents a systematic review of web-based health information systems used in chronic disease management. Literature was collected from PubMed, IEEE Xplore, and Google Scholar and selected based on predefined criteria. The results show that these systems improve patient monitoring, medication adherence, communication between patients and healthcare providers, and medical data management efficiency. Key features such as electronic health records, remote monitoring, and web-based health education support clinical decision-making and patient self-management. However, challenges related to data security, system interoperability, and user adoption remain. Overall, web-based health information systems show strong potential in enhancing chronic disease management, although further improvements are needed to ensure secure, user-friendly, and integrated healthcare systems.